CORRELATION BETWEEN ANTHROPOMETRIC MEASUREMENTS AND RISK OF ANEMIA AMONG RURAL COMMUNITY IN CANGKRINGAN, SLEMAN - Dita Maria Virginia; Fenty Fenty (Sanata Dharma University, 2017)
Anemia has been detected on various age groups. Measurement of hemoglobin (Hb) levels is a standard for deciding anemia conditions. The measurement requires certain costs, medical professional, and is invasive. People in rural areas need an economical, easy and simple examination to identify the risk of anemia. Anthropometric measurement is expected to be an appropriate measurement model for rural communities. The objective of the study is to obtain the best anthropometric measurement predictors for detecting anemia in rural communities. This was an observational study using a cross-sectional design. The inclusion criteria of the subjects of the study were residents of Cangkringan, who were between 40 and 60 years old. The subjects were chosen using random sampling cluster technique. The sample size was 100 respondents and was taken based on cluster. Descriptive analysis was used to determine the prevalence of anemia. Analysis the difference in proportion was conducted using Mann-Whitney. Correlation analysis was performed to determine the relationship between Hb levels and anthropometric measurements by using Spearman. The results showed that only 5% of the subjects are in the status of anemia based on their Hb levels. There is a significant difference between Hb levels in the normal and obese groups based on the waist hip circumference ratios (WHR) (p = 0.002). The waist circumference has a weak correlation (r = 0.238, p = 0.017) and WR has a moderate correlation (r = 0.483, p = 0.000) with Hb levels. The results of this study are not appropriate in which central obese patients should be more at risk of anemia. This study concludes that there is a significant positive moderate correlation between anthropometry, which is the waist circumference parameters and WHR, to the Hb levels in rural communities.